The importance of the humanities in shaping a realistic relationship between humans and nature - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2018)
Along with the deepening of the ecological crisis, our understanding of its nature is also increasing. While the analysis of its causes and effects, along with the development of a strategy to overcome it, was at first carried out solely by representatives of the natural and technical sciences, it has now been undertaken also by humanists, artists and cultural and religious leaders. The joining of humanists in this endeavour enables better recognition of the nature of the ecological crisis and consequently helps to develop a more adequate strategy to counteract its impact. Particularly noteworthy is the contribution of world religions in shaping a realistic relationship between humanity and nature. This article points to the increasing humanisation of the ecological reflection and offers examples of the commitment demonstrated by representatives of various religious traditions to the protection of forests